2010
DOI: 10.1159/000314897
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, Etiology, Diagnosis, and Management of Camptocormia

Abstract: Camptocormia (bent spine syndrome, cyphose hystérique) is an abnormality characterized by severe forward flexion of the thoracolumbar spine which typically increases during walking or standing and completely disappears in supine position. Camptocormia can be due to central nervous system diseases, such as Parkinson’s disease, dystonia, multisystem atrophy, or Alzheimer’s disease, due to peripheral nervous system diseases, such as primary myopathy, secondary myopathy, motor neuron disease, myasthenia, or chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 137 publications
1
59
0
14
Order By: Relevance
“…The presence of such abnormalities might imply a possible -perhaps only secondarymyopathologic phenomenon [22,24,25,37] . Finsterer and Strobl [38] noted in their review that the frequently observed myopathic abnormalities on electromyography or muscle biopsy in parkinsonian patients with CC are attributed to chronic contractions of the antigravity mus-cles involved in compensatory trunk extension, rather than a primary myopathy. However, as pointed out in the statement by Deuschl et al [37] , there is strong evidence that the cause of CC is a locally restricted myopathy, with no clear understanding of how this is caused.…”
Section: Cc/dhs -Symptom Of a Myopathy?mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of such abnormalities might imply a possible -perhaps only secondarymyopathologic phenomenon [22,24,25,37] . Finsterer and Strobl [38] noted in their review that the frequently observed myopathic abnormalities on electromyography or muscle biopsy in parkinsonian patients with CC are attributed to chronic contractions of the antigravity mus-cles involved in compensatory trunk extension, rather than a primary myopathy. However, as pointed out in the statement by Deuschl et al [37] , there is strong evidence that the cause of CC is a locally restricted myopathy, with no clear understanding of how this is caused.…”
Section: Cc/dhs -Symptom Of a Myopathy?mentioning
confidence: 99%
“…Levodopa might induce dystonic symptoms preferentially in high doses and/or in cases of long-treatment duration [7,8,15,32] . During the course of the disease, drug-induced motor fluctuations occur due to narrowing of the therapeutic window, and these alterations could be improved by changing the mode of levodopa delivery so as to ensure continuous and stable supply of the drug to the brain [38] . Up to now, there are no general treatment strategies, some authors report that continuous intravenous, subcutaneous or duodenal infusion with both levodopa and dopamine agonists improves CC [12,30] .…”
Section: Drug-induced CCmentioning
confidence: 99%
See 1 more Smart Citation
“…Many possible causes of camptocormia have been reported, including muscle rigidity and dystonia in the abdomen, proprioceptive deficits, adverse effects of dopamine agonists, soft tissue imbalance, and fatty degeneration and myopathy in the back muscles, but details remain unclear [7]. Although there is no effective curative therapy, several symptomatic therapies are reported to be effective, including dosage of oral carbidopa/levodopa or dopamine agonists, botulinum toxin injections, and DBS [3,[8][9][10][11]. Meanwhile, pain in the low back and legs is common in Parkinson's disease, with a prevalence of approximately 40-85% [3].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this combination of muscle involvement in lower and upper limbs composes a constant pattern and represents a signature of NLSD-M in all stages of the disease. In the clinical context, muscle MRI may help to recognize NLSD-M among different conditions affecting predominantly proximal upper limbs with neck extensor weakness (''man in the barrel'' or ''dropped head'' syndromes) [31][32][33][34] or among different metabolic myopathies, notably those associated with lipidosis on the muscle biopsy [35]. Nevertheless, more muscle imaging data are needed from these other conditions to establish if the ''MRI signature'' in NLSD-M is specific when compared to other muscle lipidosis.…”
Section: Discussionmentioning
confidence: 99%